Number symbolism in the magic texts of Ukrainian charms - Shuliak, S.; S. Sovhira, S. Sovhira, (Opción, 2019)
The article investigates the symbolic values of sacral numbers in the magic texts of Ukrainian charms via comparative qualitative research methods. In result, the myth numbers are defined as a means of magic ordering the world. In conclusion, the number symbolism in the texts of Ukrainian charms is indisputable. A special symbolism is given to the numbers of the first ten, one, two, three, four, and seven, which is provided by their significance in the picture of the world of Ukrainians.